Characteristics and Potential Indigenous Bacteria Isolated from Shallot Farming in Brebes Regency as Diazinon Pesticide Remediation Agents - Purbalisa, Wahyu; Hendrayanti, Dian; Yusuf, Wahida Annisa (UI Scholars Hub, 2025)
Diazinon is an organophosphate pesticide that is widely used by shallot farmers in Brebes Regency. Due to its toxicity, diazinon residue in agricultural lands as well as plants’ cultivation is harmful to humans and the environment. Using indigenous soil bacteria as a remediation agent is an alternative solution to overcome diazinon contamination. Firstly, this study aimed to characterize isolates from diazinon-contaminated shallot farming. The second objective was to test the diazinon tolerance of the isolates in various diazinon concentrations. Isolation was carried out using nutrient agar (NA) media containing diazinon concentrations of 5, 25, 50, and 100 ppm. The characterization of isolates was based on morphology and physical chemistry, including gram staining, catalase-oxidase, and carbohydrate fermentation tests. A hypersensitive test was conducted to ensure the non-pathogenic properties of the isolates. Diazinon degradation was tested using gas chromatography. This study successfully obtained 10 isolates, six of which were Gram-positive bacteria. The colonial shapes were various, including circular, filamentous, and irregular. All isolates were neutrophilic bacteria, positively reacted to catalase tests, and could use glucose in carbohydrate fermentation tests. The hypersensitive test demonstrated that all isolates were non-pathogenic. All isolates adapted to various concentrations of diazinon up to 50 ppm. The highest diazinon degradation (82.2%) was performed by Gram positive-filamentous strain KD1-D100.1. The application of indigenous isolates in this research will be studied further by testing the single and consortium inoculation for soil remediation.